Association and Joint Optimization of max-dmin Precoder with MIMO Turbo Equalization - Nhan, Nhat-Quang; Rostaing, Philippe; Amis, Karine; Collin, Ludovic; Radoi, Emanuel (2015 IEEE Global Communications Conference (GLOBECOM), 2015)
In this paper, we investigate the concatenation of the multiple input multiple output (MIMO) maxdmin linear precoder with an outer forward error correction (FEC) code at the transmitter. At the receiver side, the turbo equalization is taken into account, which iteratively exchanges the extrinsic information between a minimum mean square error interference canceller (MMSE IC) and a FEC decoder. The analysis done by extrinsic information transfer (EXIT) chart shows that a higher mutual information (MI) at the convergence state of the turbo equalization is observed thanks to the linear precoder. In addition, we exploit this property to propose a new precoder named maxdminMOD. Numerical simulations are in accordance with the theoretical analysis, which exhibits a significant improvement of the error- rate of the turbo equalization as well as a significant gain of maxdminMOD compared to original maxdmin precoder.